Anchored inflation expectations - Carlos Viana de Carvalho; Stefano Eusepi; Emanuel Mönch; Bruce Preston (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2021)
We develop a theory of low-frequency movements in in ation expectations, and use it to interpret joint dynamics of in ation and in ation expectations for the United States and other countries over the post-war period. In our theory long-run in ation expectations are endogenous. They are driven by short-run in ation surprises, in a way that depends on recent forecasting performance and monetary policy. This distinguishes our theory from common explanations of low-frequency properties of in ation. The model, estimated using only in ation and short-term forecasts from professional surveys, accurately predicts observed measures of long-term in ation expectations and identifies episodes of unanchored expectations.
Keywords: E32; D83; D84; 330; Anchored expectations; ination expectations; survey data